1995
DOI: 10.1111/j.1600-0560.1995.tb01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging versus intrinsic aging: A morphologic assessment of facial skin*

Abstract: Histologic studies have become increasingly important in recognizing morphologic differences in photoaged versus intrinsically aged skin. Earlier histologic studies have attempted to evaluate these changes by examining anatomical sites which are not comparable, such as face and buttocks. As part of a multicenter study, we have quantitatively examined a panel of 16 histologic features in baseline facial skin biopsies from 158 women with moderate to severe photodamage. When compared to the postauricular area (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 15 publications
5
86
1
6
Order By: Relevance
“…11 On pathology, sun-exposed skin shows statistically increased number of melanophages in the dermis when compared with photoprotected skin. 12 Similar findings are seen in poikiloderma of Civatte. 13 We identified melanophages in the papillary dermis of PXE-like PDE in nearly all cases (88.2%).…”
Section: Discussionsupporting
confidence: 82%
“…11 On pathology, sun-exposed skin shows statistically increased number of melanophages in the dermis when compared with photoprotected skin. 12 Similar findings are seen in poikiloderma of Civatte. 13 We identified melanophages in the papillary dermis of PXE-like PDE in nearly all cases (88.2%).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies that have been reported in the literature measured the melanin content for various skin types and suggest that p mel ranges from approximately 3% for light skin to 50% for dark skin. [31][32][33][34][35] We represent light, moderately pigmented, and dark skin by using the values p mel ϭ 5, 25, 50%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In habitually sun-exposed skin keratinocytes vary in size and shape with clusters of p53-positive cells [5], though not all studies show this [6]. Melanosome distribution among keratinocytes is irregular [7], and increases in melanin content and in melanocytic atypia are often found [8]. There is also a flattening of the rete ridges, the finger-like protrusions at the dermal-epidermal junction (DEJ) interface [4].…”
Section: Introductionmentioning
confidence: 99%